Origin Stories in Political Thought : Discourses on Gender, Power, and Citizenship - Wright, Joanne H. (Joanne Harriet), 1966- (Book collections on Project MUSE., 2004)
"Joanne H. Wright's Origins Stories in Political Thought examines Plato's Timaeus, Hobbe's story of the state of nature and the social contract, and early Second Wave feminist stories about the beginnings of patriarchal social relations. Using a historically sensitive, feminist methodology, Wright documents and deconstructs the tradition of telling origin stories in the larger history of political thought." "Although individual tales have been assessed in current scholarship, the motif of the origin story itself has, until now, escaped systematic analysis. With meticulous research and convincing conclusions, Origin Stories in Political Thought makes a valuable contribution to both feminist and political studies."--Jacket